Women’s sport and emancipation – about the first Polish Olympians - Pędraszewska, Barbara (Physical education, sport and olympism from a pedagogical perspective, 2023)
Modern Olympism grew out of admiration for the idea of the ancient Olympic Games. It was preceded by the development of gymnastic systems and enhanced sports forms in the form of associations and clubs operating in the 19th century. The place of sport used in social life in many countries, unfortunately, the presence in this field was the domain of men. Thanks to the emancipation movement, women were heading for equality, also in the field of sports. This text shows the beginning of the activity of Polish female athletes in the Olympic Games in the interwar period and the inclusion of women in world sport.